The impact of cafeteria feeding during lactation in the rat on novel object discrimination in the offspring - Wright, Thomas; King, Madeleine; Davey, William; Langley-Evans, Simon C.; Voigt, Jörg-Peter (Cambridge University Press, 2014)
There is increasing evidence that hyperenergetic diets impact on memory in rodents. However, it is largely unknown how diets, such as a cafeteria diet (CD), that mimic a Western diet act on learning and memory, in particular when fed during early stages of development. Here, we fed lactating dams a cafeteria diet and exposed both male and female offspring to a novel object discrimination (NOD) task, a two-trial test of recognition memory in which rats exposed to two identical objects during a training/familiarisation trial can discriminate a novel from a familiar object during the subsequent choice trial. The choice trial was performed following inter-trial interval (ITI) delays of up to 4 h. Maternal diet did not impact on exploration of the objects by either sex during the familiarisation trial. Control males discriminated the novel from the familiar object indicating intact memory with an ITI of 1h, but not 2 or 4h. CD delayed this natural forgetting in male rats such that discrimination was also evident after a 2h ITI. In contrast, control females exhibited discrimination following both 1 and 2h ITIs, but CD impaired performance. In summary, the present study shows that maternal exposure to CD programmes NOD in the adult. In better performing females dietary programming interferes with NOD whereas NOD was improved in males after lactational CD feeding.